Integrasi Nilai-nilai Islam dalam Materi Perubahan Iklim dalam Perspektif Teknologi Pembelajaran - Sartika, Septi Budi; Supriyadi; Wiguna, Akbar (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to describe theoretically and empirically the integration of Islamic values ​​in climate change material in the perspective of learning technology. The research method uses descriptive qualitative, namely the study of literature. Data collection techniques using documentation studies. The data analysis technique uses the Miles & Huberman model, which includes data reduction, data presentation, and verification and conclusion drawing. The results of the study show that technology in learning is a demand for the 21st Century and the achievement of an independent curriculum, one form of technology in learning is the use of electronic modules based android. The integration of Islamic values ​​into climate change material is to interpret an uncertain climate, Islam views that nature and its contents are creations of Allah swt that must be maintained and cared for human survival, but the attitude of humans who do not care about the balance of nature causes an imbalance of ecosystems, global warming, and climate change. The results of relevant research state that the meaning learning model is proven to be able to foster students' moral sensitivity to the surrounding environment, with the role of technology to facilitate the interpretation of abstract climate change material into Islamic values, for example with electronic-based learning media. Future research is expected to be able to develop e-modules that try to integrate Islamic values ​​into science material in Secondary Schools.